Temperature-Dependent Local Electric Field Transient Analysis and Measurement in High-Voltage Power Module Packaging - Chen, Meng; Wang, Yalin; Fan, Lu; Ding, Yi; Yin, Yi (IEEE transactions on dielectrics and electrical insulation, 2025)
Electrical field (E-field) concentration in the high-voltage power module packaging, which is one of the main causes of packaging failure, is not only highly related to the dielectric parameters of packaging insulation but is also influenced by environmental factors such as temperatures. This article focuses on the local E-field transients at various temperatures in power modules considering the thermal-electrical effects on packaging insulation properties. The experimental investigation on dielectric packaging properties is conducted and the relationship model between insulation properties and thermal-electrical effects is proposed. Based on the proposed model, the E-field transient is analyzed in the typical half-bridge power module by simulation. The results show that the positions with square wave voltage output are subject to the most severe stress, followed by positions with constant direct current (dc) voltage. The interfacial charge relaxation is responsible for the different E-field transients at various positions subjected to different voltage stresses. Besides, the maximum local E-field exhibits an exponential increase with temperature. In addition, an experimental E-field measurement method is first applied in the power module to study the influence of temperature on the local E-field. The experimental results further indicate an exponential relationship between the maximum E-field and temperature. Furthermore, the trend of increasing E-field with rising temperature is more pronounced in the experiments compared with the simulations. This may be attributed to more significant charge injection during the experiments. The research provides valuable insights into the E-field evolution mechanism in high-voltage power modules regarding the thermal-electrical effects.